ISSUE BRIEF. EMPLOYMENT DISCRIMINATION AND SMOKER ACCOMMODATION. (Tufts Archival Research Center, 2007)
Issue Brief on Employment Discrimination and Smoker Accommodation recognizing that the tobacco industry has turned from defending the rights of smokers to promoting an affirmative strategy to protect the interests of its customers. Cites that smoking discrimination would also indirectly affect minorities and blue collar workers because they smoke in greater numbers. States the objective to accommodate the needs of both smokers and nonsmokers. Lists proponents and opponents of employment discrimination legislation.